PROSES PEMBENTUKAN IDENTITAS SANTRI PADA REMAJA PONDOK PESANTREN SALAFIYAH SYAFI'IYAH SITUBONDO - Mohamat Hadori1 (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2012)
This study aims toobserve the processof Islamic student (santri) identity formationin adolescent of Islamic boarding school (Pesantren) of SalafiyahSyafi'iyahSitubondo East Java. This study usedin-depth interviewstocollect datafromthe 4 participantsand 6informants. There are fourprocesses which must be done in a researchusing qualitative method of phenomenology. They are theepoche, phenomenologicalreduction,imaginativevariation, andsynthesisofmeaning. The results showedthat participantsin undergoingtheir self-identity formation process as muslimstudentsare influenced by their own personalityin addressingthe application of the Pesantren rules,various activities required, the parenting style ofdormitory leader, andthe presence ofpeers. Threeparticipantsin undergoingthe process of establishingtheir self-identity formationasstudentswere in the stage of identity moratoriumand oneparticipantwas in the stageof identityachievement.